Maria Teresa Kopschitz de Barros and Maria Thereza Peixoto Kopschitz (eds.). Passos de Maria Helena Kopschitz. - Daghlian, Carlos (ABEI Journal, 2015)
Maria Teresa Kopschitz de Barros and Maria Thereza Peixoto Kopschitz (eds.). Passos de Maria Helena Kopschitz. Niteroi: ZIT Gráfica, 2014. 180 pp.